Relationships between Physical Activity and other health behaviours in pre-registration nurses in Nottingham - Pisano, Charlotte (2008)
Objective: To determine if pre-registration nurses achieve physical activity levels recommended by the government and the rationale as to why it is important as well as to ascertain if there is an association between levels of physical activity and other health behaviours of pre-registration nurses and the rationale for these.